Biochemical characterization of Nostoc sp. exopolysaccharides and evaluation of potential use in wound healing. (15th February 2021) - Alvarez, Xavier; Alves, Andreia; Ribeiro, Maximiano P.; Lazzari, Massimo; Coutinho, Paula; Otero, Ana
Graphical abstract: Highlights: Acetate enhanced the production of anionic EPS by Nostoc spp. PCC7913 and PCC7936. The EPS presented galacturonic acid and sulphate groups with a MW > 1000 kDa. Gelation of the EPS was obtained by addition of FeCl3. The EPS promoted fibroblast proliferation and migration in in vitro scratch assays. Nostoc sp. anionic EPS could be used as a biomaterial for wound-healing dressings. Abstract: Exopolysaccharides (EPS) produced by cyanobacteria are complex biomolecules of anionic nature with potential biomedical applications. In this study, the EPS produced by the Nostoc sp. strains PCC7936 and PCC7413 were characterized and evaluated as a biomaterial for new wound dressings. The addition of acetate ions to the culture medium slightly stimulated EPS production, achieving 1463.1 ± 16.0 mgL -1 (PCC7413) and 1372.1 ± 29.0 mgL -1 (PCC7936). Both EPS presented nine monosaccharide residues and a MW > 1000 kDa. The acetate addition changed the monosaccharide molar percentages. FTIR and DLS results confirmed the anionic nature and the presence of sulfate groups in both EPS, which are determinant features for biomedical applications. Both EPS at 1%(w/v) formed gels in the presence of 0.4%(w/v) FeCl3 . Results obtained for MTT assay and wound healing in vitro scratch assay revealed hydrogels biocompatibility and ability to promote fibroblast migration and proliferation that was greater in PCC7936. The Nostoc EPS hydrogels presented promising properties to be applied in the treatment of skin injuries.